Conviviality, rights, and conflict in Africa’s urban estuaries - Landau, LB (SAGE Publications, 2014)
Varied forms of mobility are rapidly transforming communities across the world. In Africa’s cities and urban peripheries, the results of human movements include ever more diverse sets of new arrivals living alongside longer-term residents as they seek protection, profit, and passage elsewhere. Some move on and others return home, while still others shift within in search of new opportunities or security. In the absence of muscular state institutions or dominant cultural norms, these areas have become estuarial zones in which varied communities of convenience are taking shape. Unlike well-documented urban gateways or ghettos, these communities range from radical forms of exclusion to remarkable modes of accommodation that enable people to extract usufruct rights: to live in but not become fully part of the cities they occupy. Using examples from Maputo, Johannesburg, and Nairobi, this article explores the nature of these estuaries in ways that challenge the conceptual foundations typically informing debates over migrant rights, integration, and the boundaries of belonging. This means eroding clear distinctions between hosts and guests along with a call to reevaluate the relative importance of state institutions and policies. Most fundamentally, it questions new residents’ interests in localized political and social recognition and participation. The article concludes by suggesting the need to reconsider the forms and scale of community through which the newly urbanized claim rights and the nature of the rights they desire.